Chervinsky Leonid Stepanovych (to the 75th anniversary of his birth) (Energy and Automation, 2025)
Leonid Stepanovych Chervinsky was born on March 16, 1950. In 1977, he graduated with honors from the Ukrainian Agricultural Academy with a degree in “Agricultural Electrification”, received the qualification of an electrical engineer and was left to work at the academy at the Department of the Application of Electricity in Agriculture, where he has been working for 48 years.